2021
DOI: 10.46754/jssm.2021.06.023
|View full text |Cite
|
Sign up to set email alerts
|

GENETIC IDENTIFICATION OF WHITE-HANDED GIBBONS (Hylobates Lar) IN CAPTIVITY

Abstract: Accordingto Groves (2001), andMootnick (2006), these five subspecies exhibit different morphological characteristics (Table 1).Systematic relationships in gibbons are still controversial. Previous investigations on the chromosomal, morphological, and behavioral features of gibbons have been utilized to attempt to resolve this. Garza and Woodruff (1992) reported mitochondrial Cytochrome b (Cyt b) variations in Hylobates. Other investigators also utilized partial mitochondrial genes to study interspecific and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…The phylogenetic positioning of H. lar within the genus Hylobates concurs with findings from previous studies (Israfil et al 2011;Chan et al 2013;Matsudaira and Ishida 2021). Our phylogenetic and network analysis showed that H. l. vestitus from Sumatra diverged first (Thinh et al 2010;Aifat and Md-Zain 2021;Matsudaira and Ishida 2021) before the proto-H. lar bifurcated to form the H. l. lar clade and the possible Indochinese subspecies clade (entelloides, carpenteri, and yunnanensis). However, the Indochinese subspecies clade did not show any obvious subspecies groupings.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The phylogenetic positioning of H. lar within the genus Hylobates concurs with findings from previous studies (Israfil et al 2011;Chan et al 2013;Matsudaira and Ishida 2021). Our phylogenetic and network analysis showed that H. l. vestitus from Sumatra diverged first (Thinh et al 2010;Aifat and Md-Zain 2021;Matsudaira and Ishida 2021) before the proto-H. lar bifurcated to form the H. l. lar clade and the possible Indochinese subspecies clade (entelloides, carpenteri, and yunnanensis). However, the Indochinese subspecies clade did not show any obvious subspecies groupings.…”
Section: Discussionsupporting
confidence: 90%
“…A total of 1030-bp of the complete CR of mtDNA was successfully obtained from all 12 samples used in this study using the newly designed pairs of oligonucleotides. The CR segment of mtDNA is the most variable region and has been recommended as the appropriate segment to be used to infer gibbon phylogeny ( Roos and Geissmann 2001 ; Woodruff et al 2005 ; Whittaker et al 2007 ; Matsudaira and Ishida 2010 ; Aifat and Md-Zain 2021 ). However, due to the lack of complete CR sequences of Hylobates in GenBank, a total of 527-bp of aligned dataset were analysed from 100 sequences representing all species of Hylobates except H. funereus .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations